The development of female students’ flexibility engaged in choreography - Olga Limanskaya; Irina Kriventsova; Vadym Altukhov; Tatiana Yermakova; Wladyslaw Jagiello; Sergii Iermakov; Igor Vypasniak; Bogdan Lisovskyi (Physical Education of Students, 2022)
Background and Study Aim. Choreographic exercises for the development of flexibility are a complex component of training students of the department of folk dance in the specialty "Choreography". Among such exercises are exercises of ballet gymnastics, which take into account the specifics of mobility of the joints. The aim of the study was to identify the level of general and special mobility (“en dehors”) in students who are engaged in choreography.